PTH-096 Improved outcomes of emergency admission for ulcerative colitis (uc) in england over the last decade: a ten year analysis of routine nhs data. (17th June 2017) - Shawihdi, M; Dodd, S; Grainger, R; Bloom, S; Cummings, F; Driscoll, R; Pearson, M; Williamson, P; Bodger, K
Abstract : Introduction: Hypothesis: Over the last decade, therapy advances and a national audit programme should have improved outcomes for UC patients admitted as emergencies (Em). Method: To support IBD Registry analytics, we have developed metrics from routine NHS data to allow reporting of trends in national-level indicators of IBD care. Design: Retrospective analysis of 10 years of HES data for England. Target population: 54, 533 Em. admissions with UC as primary diagnosis (April '05 to March '13; n=37 170 patients). Binary Outcome Measures : Surgery (colectomy) during index admission (Sx-Index) or within 1 year (Sx-1-Year); Em. readmission within 30 days of discharge (Readmit-30d); Inpatient death during index admission (Death-Index). Case-mix Variables : Age, Gender, Co-morbidities (0, 1 or 2+, Charlson), Deprivation Status (IMD Quintiles), Any Cancer, Em. bed bays (all-cause) in preceding year (EmBedDaysLastYr). Predictor Variable: Year of Admission (Yr-Adm). Analyses: Uni- and multivariable logistic regression (stepwise), reporting adjusted odds ratios (OR ) for retained variables. Adjusted for repeat admissions in same patient (clustered standard errors). Results: Multivariable Models : OR for Sx-Index was reduced with increased age (0.98 per yr), 2+ co-morbidities (0.81 vs. none), females (0.74 vs. male) and for >28 EmBedDaysLastYr. OR for Death-Index was increased with increased age (1.10 per yr), co-morbidities (1.87 for one, 3.2 for two or more, vs none) and colectomy during admission (6.99 vs. no surgery) but reduced for >28 EmBedDaysLastYr (0.88 vs. none). Models for Sx-1-Year showed a similar pattern with respect to reduced OR for age, co-morbidity and females. For Readmit-30d, the most significant factor associated with r educed OR was colectomy during admission (0.43), whereas >28 EmBedDaysLastYr was associated with increased OR (2.0 vs. none). Deprivation status was not independently associated with any outcome. After adjusting for these co-variates, Yr-Adm was associated with a significant reduction in OR for both Sx-Index and Death-Index, with OR of 0.98 (0.976–0.998) and 0.91 (0.88, 0.94) per yr relative to base year. Models for all-cause admissions did not show these trends, suggesting condition-specific findings. Conclusion: Risk of colectomy and inpatient death for UC patients admitted as emergencies to English hospitals has reduced over the last 10 years. Many factors may explain these trends, but cycles of UK-wide IBD audit are likely contributors. We found no signal for social inequality, but a reduced odds of surgery for females requires further study. Funding: Crohn's and Colitis UK Disclosure of Interest: M. Shawihdi: None Declared, S Dodd: None Declared, R Grainger: None Declared, S Bloom: None Declared, F Cummings: None Declared, R Driscoll: None Declared, M Pearson: None Declared, P Williamson: None Declared, K Bodger Conflict with: AbbVie, Conflict with: Boston Scientific | Takeda